Strategic Planning in Decision Making Against the Information Perspective - Yusuf Hadijaya; Fazli Abdillah; Fima Muhazri Sembiring; Sri Muliyani (Edumaspul: Jurnal Pendidikan, 2022)
The development of science and information technology has changed the perspective and lifestyle of the Indonesian people in carrying out their activities. The existence and role of information technology has brought a new era of development in all fields, but these developments have not been matched by an increase in human resources that determine the success of the institution's goals. Information is any form of communication that adds understanding and knowledge, which is useful for the recipient of the information. Information is like blood that flows in the body of an organization. The source of information is data, namely facts that describe real events and real entities. Data is a raw form that cannot tell much, so it needs to be processed further. Data is processed through a model to produce information. Strategic planning is a process carried out by an organization to determine strategy or direction, and make decisions to allocate its resources to achieve the strategy. The term strategic planning was originally known among the military, in this case it implies planning operations to the opponent's area by taking into account all the possibilities, advantages and disadvantages and taking into account the real conditions they have and the existing environmental conditions by trying to take into account the opponent's strengths so that the military operation is carried out. worked out well.